Análise do ciclo de vida da usina hidrelétrica de Curuá-Una (Baixo Amazonas, Brasil) - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2016)
Brazil as well as the rest of the world, faces a major challenge related to the electricity sector, to meet the growing demand with energy production from renewable sources. Many hydroelectric plants are being implemented, especially in the northern region of Brazil, where river basins have still great potential to be explored. However, the question about the environmental impacts of hydroelectric dams is still not fully known, and more detailed and specific studies of this technology are needed. Thus, the objective of the present study is the investigation of environmental impacts of the construction, operation and decommissioning of a hydroelectric power station based on Life-Cycle Assessment. The main focus is the Curuá-Una hydropower plant wich is located in the Amazon forest in northern Brazil, in Santarém municipality (Pará state). The results are presented in relation to production having as functional unit 1 MWh, so that comparisons can be made. The categories analyzed were: Acidification Potential, Global Warming Potential, Abiotic Depletion Resources, Freshwater Aquatic Ecotoxicity Potential and Human Toxicity Potential. Results for Life Cycle Analysis show the construction phase as most influential to emissions and the inputs that contribute most to these emissions are steel and concrete. Considering the productivity factor, the indices found in the scenario of higher productivity were lower than in the scenario of lower productivity. The comparison of the ACV results of the Curuá-Una HPP with ACVs of studies that analyzed other energy production technologies indicates that for the analyzed categories the hydroelectric plant has a good environmental performance, considering the emissions quantified by this methodology.
Keywords: Energia elétrica; Usina Hidrelétrica de Curuá-Una - PA; Impacto ambiental; Análise do Ciclo de Vida; Baixo Amazonas; CNPQ::ENGENHARIAS::ENGENHARIA ELÉTRICA::SISTEMAS ELÉTRICOS DE POTÊNCIAS; SOCIEDADE, NATUREZA E DESENVOLVIMENTO